Le Fort I Down-Fracture for Management of Midface Tumors - Quirino, Lilian Caldas [UNESP]; Carvalho, Pedro Henrique de Azambuja [UNESP]; Santos, José Cleveilton Dos [UNESP]; Trento, Guilherme Dos Santos [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Wolters Kluwer, 2020)
OBJECTIVE: To perform an integrative review associating current literature with a clinical series regarding the use of Le Fort I osteotomy for the removal of tumors located in the midface and central region of the skull base. METHODS: A systematic review was performed through the PubMed, SCOPUS, and Cochrane databases. In addition, 4 different patients operated using the above-cited technique are described in this study. RESULTS: Initially, 123 articles were found. After the removal of duplicates, and title and abstract reading, 27 articles were selected for data extraction. The Le Fort I surgical approach of tumors was performed in 183 patients. CONCLUSION: The Le Fort I surgical approach allows lesion exeresis with good visualization, low rates of recurrences and complications, and without aesthetic compromises for the patient.